Esoteric Connective Tissue Therapy for chronic low back pain to reduce pain, and improve functionality and general well-being compared with physiotherapy: study protocol for a randomised controlled trial - Christoph Schnelle (Trials, 2017)
Abstract Background Low back pain causes more global disability than any other condition. Once the acute pain becomes chronic, about two-thirds of sufferers will not fully recover after 1–2 years. There is a paucity of effective treatments for non-specific, chronic low back pain. It has been noted that low back pain is associated with changes in the connective tissue in the affected area, and a very low-impact treatment, Esoteric Connective Tissue Therapy (ECTT), has been developed to restore flexibility in connective tissue. ECTT uses patterns of very small, circular movements, to the legs, arms, spine, sacrum and head, which anecdotally are effective in pain relief. In an unpublished single-arm phase I/II trial with chronic pain patients, ECTT showed a 56% reduction in pain after five treatments and 45% and 54% improvements at 6 months and 7–9 years of follow-up respectively. Methods The aim of this randomised controlled trial is to compare ECTT with physiotherapy for reducing pain and improving physical function and physical and mental well-being in patients with chronic low back pain. The trial will be held at two hospitals in Vietnam. One hundred participants with chronic low back pain greater than or equal to 40/100 on the visual analogue scale will be recruited and randomised to either ECTT or physiotherapy. Four weekly treatments will be provided by two experienced ECTT practitioners (Treatment Group, 40 minutes each) and hospital-employed physiotherapy nurses (Control Group, 50 minutes). The primary outcomes will be changes in pain, physical function per the Quebec Pain Functionality Questionnaire and physical and mental well-being recorded by the Short Form Health Survey (SF-36), with mixed modelling used as the primary statistical tool because the data are longitudinal. Initial follow-up will be at either 4 or 8 months, with a second follow-up after 12 months. Discussion The trial design has important strengths, because it is to be conducted in hospitals under medical supervision, because ECTT is to be compared with a standard therapy and because the assessor and analyst are to be blinded. The findings from this trial will provide evidence of the efficacy of ECTT for chronic low back pain compared with standard physiotherapy treatment. Trial registration Australian New Zealand Clinical Trials Registry, ACTRN12616001196437 . Registered on 30 August 2016.